Technology blueprint for clip tower mini air cooler / Afiqah binti Abd Aziz - Abd Aziz, Afiqah (2020)
Nowadays, there are some people cannot afford to buy air conditioner that is increasingly sophisticated. Therefore, the Clip Tower Air Cooler can help the consumer to have air cooler in exchange to air conditioner that are affordable and easy to use. Overall marketing strategy will be included specific marketing philosophy and strategy of the company, the value chain and the channel of distribution in the target market. First of all, company target will be based on the residence in Shah Alam area since the company is nearby Shah Alam. For initial, intensive selling effort, company has set the target customer in other words, types of customer groups that would buy this product.